2007
DOI: 10.1097/01.gme.0000248707.53075.7f
|View full text |Cite
|
Sign up to set email alerts
|

Early postmenopausal hormone therapy improves postural balance

Abstract: Initiation of HT soon after menopause rapidly improved postural balance to levels normally seen in young women. We suggest that improved postural balance can contribute to the protection against fractures associated with HT and explain the more substantial reduction in hip fracture risk after HT initiated sooner, compared with later, after menopause. Further study is required to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 44 publications
3
16
0
5
Order By: Relevance
“…For the female participants in the present study these fluctuations could be partly caused by changes in estrogen levels. In support of this notion, several studies have reported that postural balance was positively affected by increased levels of plasma estrogen [31][32][33]. In addition, estrogen secretion follows a diurnal pattern with elevated plasma levels in the morning that gradually decreases throughout the day [34].…”
Section: Subject Characteristicmentioning
confidence: 75%
“…For the female participants in the present study these fluctuations could be partly caused by changes in estrogen levels. In support of this notion, several studies have reported that postural balance was positively affected by increased levels of plasma estrogen [31][32][33]. In addition, estrogen secretion follows a diurnal pattern with elevated plasma levels in the morning that gradually decreases throughout the day [34].…”
Section: Subject Characteristicmentioning
confidence: 75%
“…After such age range, a gradual deterioration in performance was observed [24]. Increased postural oscillation was shown in women older than 55 years, which is consistent with the increased number of forearm fractures [25]. Vision is most often needed for postural stability maintenance, particularly among older persons [2].…”
Section: Discussionmentioning
confidence: 92%
“…However, the mean age (54.2 y) was substantially lower in the previous studies and the dose of tibolone used (2.5 mg/d) was higher, twice that used in our study. It seems to be easier to affect some outcomes if treatment is undertaken close to menopause, as previously described for postural balance function 11 and progression of atherosclerosis in the artery wall. 35,36 Proximity to menopause could therefore explain the positive effects of tibolone on muscle strength in the previous report.…”
Section: Discussionmentioning
confidence: 98%
“…7 Multiple-component group exercise regimens reduce the incidence of falls and the risk of falling, as do tai chi and individually prescribed multicomponent home-based exercise programs. 8 Postmenopausal hormone therapy (HT) increases bone mass, 9 improves postural balance, [10][11][12] and reduces fracture risk, 13 but the risk of fracture returns rapidly to baseline after stopping therapy. [14][15][16][17] Whether HT in older women can improve postural balance and/or muscle strength and function, and thus reduce the risk of falls and fracture, is a very important question because most fractures occur in older people.…”
mentioning
confidence: 99%